Real Interest, Money Surprises, Anticipated Inflation and Fiscal Deficits - Makin, John H. (The Review of Economics and Statistics, 1983)
THE hypothesis attributed to Fisher (1930) and more recently the innovative investigation by Fama (1975) have predisposed many economists to treat the expected rate of interest as a constant. At the very least, as a magnitude, the expected interest rate is appealingly viewed as being independent of monetary phenomena. The late 1970s and early 1980s have produced events which force reevaluation of the maintained hypothesis of constancy of the expected rate (hereafter referred to as the real rate). For example, from December 1980 to June 1981 the expected rate of inflation fell by 165 basis points from an annual rate of 10.51 % to an annual rate of 8.86%.' Over the same period 3 month Treasury bill rates continued to remain largely between 14% and 16% with average yields of 15.02% in December 1980 and 14.95% in June 1981. In order to reconcile such facts, one must either believe that security markets no longer fully reflect changes in anticipated inflation in nominal market rates, or that a large drop in anticipated inflation which is not accompanied by a drop of similar magnitude in nominal interest rates, is due to an offsetting rise in the rate.2 Statistical investigations regarding the possibility of movements in the rate have appeared with increasing frequency since publication of Fama's (1975) provocative article.3 Nelson and Schwert (1977) argued that Fama's test of the joint hypothesis of market efficiency and constancy of the rate was not sufficiently powerful and after applying more powerful tests concluded that the data permitted rejection of the hypothesis of constancy of the rate. Other investigations including those by Carlson (1977), Garbade and Wachtel (1978) and Levi and Makin (1979) have rejected the hypothesis of constancy of the rate while tending to support the hypothesis that market interest rates include an efficient inflationary premium. Tanzi (1980) has, along with others, emphasized the role of taxes in interest rate determination. More recently investigators have moved from merely testing the hypothesis of constancy of the rate to searching for an explanation for the rate movements suggested by a large body of statistical evidence. Mishkin (1981) and Fama and Gibbons (1982) have investigated the relationship between the rate and anticipated inflation suggested by Mundell (1963) and Tobin (1965).4 Levi and Makin (1979, 1981), Hartman (1981) and Hartman and Makin (1982) have considered effects of inflation uncertainty on the rate. Dwyer (1981) has found that the rate is independent of predictable changes in the supply. This paper derives a Fisher-type interest rate equation from a structural model similar to that employed by Sargent (1973) for other purposes. The primary differences involve inclusion of a government sector and a simple open economy specification along with introduction of a role for Received for publication February 22, 1982. Revision accepted for publication September 3, 1982. *University of Washington and National Bureau of Economic Research. This work was supported by the National Science Foundation under (irant No. SES-8112687. I would like to thank without implicating Charles Nelson, Richard Hartman and especially Andrew Criswell for excellent help in estimating the equations. An earlier version of this paper was presented at an FMME Conference at NBER where many useful suggestions were provided. ' This figure is based on Livingston survey data for 6 month horizon expectations regarding the consumer price index (CPI). The 12 month horizon figure for CPI also indicated a drop of 165 basis points while 6 and 12 month horizon numbers for WPI indicated drops of 192 and 174 basis points, respectively. Updated Livingston survey data are now compiled by the Federal Reserve Bank of Philadelphia. 2Summers (1982) has argued that nominal interest rates do not adjust by the full amount implied by the Fisher hypothesis modified to allow for marginal tax rates on interest earnings. His results based on both preand post-World War II data arise from equations which employ actual inflation rates in place of anticipated inflation and which generally do not include variables to control for movements in the expected rate. 3Even well before the investigations discussed here Irving Fisher himself reported, based on an investigation of market interest rates during the late 19th and early 20th centuries in London, New York, Berlin, Calcutta and Tokyo, that ' the rate of interest in terms of commodities is from seven to thirteen times as variable as the market rate of interest expressed in terms of money (Fisher (1930), p. 415). 4 Mishkin (198 1) found a significant negative impact upon the rate of a lagged actual (CPI) inflation rate taken as a proxy for anticipated inflation. An ARIMA (0, 1, 1) inflation model with a seasonal MAI term also provided an expected inflation proxy with a significant negative impact on the rate. Mishkin (1982) is discussed below.